Enhancing digital motivation work and its effect on digital target-based employee performance at regional revenue agency of DKI Jakarta province - Saputrabey, Muhamad Abrar; Sepriyanti, Yuke; Riyanto, Riyanto; Moeins, Anoesyirwan; Zen, Yuli (Edelweiss Applied Science and Technology, 2025)
This study aims to examine the influence of digital work motivation and adaptability on employee performance based on digital targets at the Regional Revenue Agency (Bapenda) of DKI Jakarta Province in the context of digital transformation. Using quantitative methods and a survey approach, this study involved 249 employees selected through proportionate random sampling techniques. The results showed that technology support, work flexibility and freedom, and digital-based work-life balance have a significant effect on digital work motivation, which ultimately increases employees' digital adaptability. This adaptability plays an important role in improving performance oriented towards digital targets, with flexibility in dealing with technological changes as a moderating factor that strengthens the relationship between operational capabilities and digital adaptability. These findings emphasize the importance of integrating technology with flexible work policies to improve employee motivation, adaptability, and performance in the public sector. This study provides a practical contribution to government agencies in designing more effective and optimal digitalization strategies.